2003
DOI: 10.1002/ange.200351573
|View full text |Cite
|
Sign up to set email alerts
|

A Homo [3+2] Dipolar Cycloaddition: The Reaction of Nitrones with Cyclopropanes

Abstract: Für Naturstoffsynthese geeignet: Cyclopropandicarbonsäurediester reagieren mit Nitronen in Gegenwart von Ytterbiumtriflat in einer [3+2]‐Cycloaddition diastereoselektiv zu Tetrahydro‐1,2‐oxazinen (siehe Schema). Mit dieser Methode lässt sich das Grundgerüst von FR‐900482 in zwei Stufen aufbauen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 28 publications
3
36
0
4
Order By: Relevance
“…This novel [3+3] cyclization of nitrones and allenes has no literature precedence, though a very recently described reaction between nitrones and electron-deficient cyclopropanes to provide tetrahydro-1,2-oxazines should be mentioned in this context. [24] Gratifyingly, additions of lithiated alkoxyallenes with nitrones are highly stereoselective, mostly giving synconfigured 1,2-oxazines under standard conditions, whereas anti compounds are produced in excess through precomplexation of the nitrones with diethylaluminium chloride. Since the received 1,2-oxazines can be transformed into a variety of cyclic and acyclic enantiopure compounds, the stereodivergent method described here is an excellent tool for efficient chain-elongations of carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…This novel [3+3] cyclization of nitrones and allenes has no literature precedence, though a very recently described reaction between nitrones and electron-deficient cyclopropanes to provide tetrahydro-1,2-oxazines should be mentioned in this context. [24] Gratifyingly, additions of lithiated alkoxyallenes with nitrones are highly stereoselective, mostly giving synconfigured 1,2-oxazines under standard conditions, whereas anti compounds are produced in excess through precomplexation of the nitrones with diethylaluminium chloride. Since the received 1,2-oxazines can be transformed into a variety of cyclic and acyclic enantiopure compounds, the stereodivergent method described here is an excellent tool for efficient chain-elongations of carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis acid catalysis was demonstrated previously for the reaction of 1 a with nitrones [13] and imines, [14] as well as in related [3+2]…”
mentioning
confidence: 95%
“…[9] Among the methods developed for the preparation of such compounds, [10] the [3+3] cycloaddition of donor-acceptor cyclopropanes with nitrones, pioneered by Kerr and co-workers, [11] is a particularly elegant approach. They found that nitrones 3 react smoothly with cyclopropanes 2 in the presence of Yb(OTf) 3 ·x H 2 O to give the cis isomers 4 diastereospecifically (see Table 1).…”
mentioning
confidence: 99%